New Direct Approaches to Robust Sound Source Localization - Rui, Yong; Florencio, Dinei (Institute of Electrical and Electronics Engineers, Inc., 2003)
When more than two microphones are used, the traditional time-delay-of-arrival (TDOA) based sound source localization (SSL) approach involves two steps. The first step computes TDOA for each microphone pair, and the second step combines these estimates. This two-step process discards relevant information in the first step, thus degrading the SSL accuracy and robustness. Although less used, one-step processes do exist. In this paper, we review these processes, create a unified framework, and introduce two new one-step algorithms. We compare our proposed approaches against existing 1 and 2-step approaches and demonstrate significantly better SSL performance.